NOVEL CRIME SCENE INVESTIGATION ACTION TO CONCENTRATE CLIENT ACTION FROM CELL PHONES - K. Jaya Rajan, M. Srinija Reddy, N. Deekshana, P. Samshritha, M. Srija (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Nowadays, mobile devices have become one of the most popular instruments used by a person in its regular life, mainly due to the importance of their applications. In that context, mobile devices store user’s personal information and even more data, becoming a personal tracker for daily activities that provides important information about the user. Derived from this gathering of information, many tools are available to use on mobile devices, with the restrain that each tool only provides isolated information about a specific application or activity. Therefore, the present work proposes a tool that allows investigators to obtain a complete report and timeline of the activities that were performed on the device. This report incorporates the information provided by many sources into a unique set of data. Also, by means of an example, it is presented the operation of the solution, which shows the feasibility in the use of this tool and shows the way in which investigators must apply the tool